Fundamental of Enterpreneurship (ENT 300) : Unplugged Coffee Cafe / Brandon Beckham Siali … [et al.] - Siali, Brandon Beckham; Abang Hasyim, Dayang Hasmiera Azreen; Larry, Nazel Isaac; Hazali, Nur Iffahanis (2019)
This case study is to summarize the company's background, the problems that they are facing, how do they manage their business and the solutions to their problems. The method used was face-to-face interviews with the owner of the cafe itself. We have chosen Unplugged Coffee Cafe as our company that we interview since we are planning to open our own coffee shop. Based on the interviews that we have done with the owner, Unplugged Coffee Cafe decided to open its business because the owner has been aiming to open a cafe that is inspired by Italian culture, and he wants to bring the Italian delicacies here